Plant Operations and Product Recalls in the Automotive Industry: An Empirical Investigation - Shah, Rachna; Ball, George P.; Netessine, Serguei (Management Science, 2017)
While there is overwhelming support for the negative consequences of product recalls, empirical evidence of operational drivers of recalls is almost nonexistent. In this study, we identify product variety (measured as the number of factory installed options), plant variety (measured as the number of models per assembly line in a plant), and capacity utilization as drivers of subsequent manufacturing-related recalls. We examine their individual and joint effects using a unique data set compiled for a seven-year period by linking assembly line production data for North American automotive manufacturers with recall data from the National Highway Traffic and Safety Administration. We show that manufacturing-related recalls are positively associated with product variety and plant utilization, but not with plant variety. We also find that the joint effect of plant variety and utilization is positively associated with increased recalls. In quantitative terms, a one-standard-deviation increase in the number of options (four additional options) is associated with two additional recalls and costs $46.2 million to automakers over the sample duration. We observe similar results with plant utilization, and find that a car built in a plant that is being utilized above 100% capacity is associated with more than eight additional recalls corresponding to an incremental cost of $167 million. This paper was accepted by Yossi Aviv, operations management.